Propellant development for small rockets - Rahmat, Mohd. Zaki Yamani; Mohd. Jaafar, Mohammad Nazri; Abdul-Latif, Ainullotfi; Wan Ali, Wan Khairuddin; Mat Yajid, Zuriana Mariati; Kimsin, Intan Noryanah (2008)
The solid propellant rocket is the basis for most recent rocket inventions where it is utilized mostly in military rockets. Solid propellants are the simplest of all rocket propulsion systems and have a variety of materials and methods for development. The purpose of this research is to develop solid propellant based on potassium nitrate, carbon, and sulphur mixture. To obtain an optimum propellant composition and performance, a number of propellant burning-rate tests have been conducted. Seven sets of propellants with different compositions have been produced using the compression method. The results obtained from the burning-rate tests show that propellants at stoichiometric composition gave the highest burning-rate of 0.2734 cm/s.